No differences in native T1 of the renal cortex between Fabry disease patients and healthy subjects in cardiac-dedicated native T1 maps - Damlin, Anna; Kjellberg, Felix; Themudo, Raquel; Chow, Kelvin; Engblom, Henrik; Oscarson, Mikael; Nickander, Jannike (Journal of cardiovascular magnetic resonance, 2024)
Fabry disease (FD) is an X-linked inherited lysosomal storage disease that is caused by deficient activity of the enzyme alpha-galactosidase A. Cardiovascular magnetic resonance (CMR) imaging can detect cardiac sphingolipid accumulation using native T1 mapping. The kidneys are often visible in cardiac CMR native T1 maps; however, it is currently unknown if the maps can be used to detect sphingolipid accumulation in the kidneys of FD patients. Therefore, the aim of this study was to evaluate if cardiac-dedicated native T1 maps can be used to detect sphingolipid accumulation in the kidneys. FD patients (n = 18, 41 ± 10 years, 44% (8/18) male) and healthy subjects (n = 38, 41 ± 16 years, 47% (18/38) male) were retrospectively enrolled. Native T1 maps were acquired at 1.5T using modified Look-Locker inversion recovery research sequences. Native T1 values were measured by manually delineating regions of interest (ROI) in the renal cortex, renal medulla, heart, spleen, blood, and liver. Endo- and epicardial borders were delineated in the myocardium and averaged across all slices. Blood ROIs were placed in the left ventricular blood pool in the midventricular slice. There were no differences in native T1 between the FD patients and the healthy subjects in the renal cortex (1034 ± 88 ms vs 1056 ± 59 ms, p = 0.29), blood (1614 ± 111 ms vs 1576 ± 100 ms, p = 0.22), spleen (1143 ± 45 ms vs 1132 ± 70 ms, p = 0.54), or liver (568 ± 49 ms vs 557 ± 47 ms, p = 0.41). Native myocardial T1 was lower in FD patients compared to healthy subjects (951 ± 79 vs 1006 ± 38, p<0.01), and higher in the renal medulla (1635 ± 144 vs 1514 ± 81, p<0.01). Compared to healthy subjects, patients with FD and cardiac involvement showed no differences in native T1 of the renal cortex. FD patients had higher native T1 in the renal medulla, which is not totally explained by differences in blood native T1 but may reflect a hyperfiltration state in the development of renal failure. The findings suggest that sphingolipid accumulation in the renal cortex in FD patients could not be detected with cardiac-dedicated research native T1 maps. [Display omitted]